Objectivity as a given. Hönigswald’s contribution to the philosophy of concrete subjectivity. - Schwind, Peter (Folia Philosophica, 2025)
This paper examines Richard Hönigswald’s contribution to a philosophy of concrete subjectivity. Its starting point is the tension between the transcendental subject and the empirically situated human being. Central to this is Hönigswald’s critical concept of objectivity: objects are not things in the world, but normative conditions for valid judgements, which are polymorphic in nature depending on the domain of reference. The general meaning of objectivity therefore lies not in an abstract form, but in the given reality of the here and now. This gives rise to anthropological implications: psychological experience, the physical organism, intersubjectivity, language and historical community appear as concretisations of transcendental subjectivity.